First report of the enset root mealybug Paraputo ensete (Williams & Matile-Ferrero) (Hem.: Pseudococcidae) on banana in Ethiopia - Fikadu Erenso; Guy Blomme; Georg Goergen; Mitiku Muanenda; Elizabeth Kearsley; Temesgen Addis (International Journal of Tropical Insect Science, 2023)
Enset root mealybugs, a major pest affecting the cultivation of the enset crop in the Ethiopian highlands, have for the first time been observed on banana mats indicating the potential host status of Musa spp. These observations were made under natural conditions in backyard gardens in the Gedeo zone, southern Ethiopia, on the root system of banana mats of the ‘Pisang Awak’ (local name ‘Feranji Muz’, ABB genome group) landrace. Here, we confirm the identification of the collected enset root mealybug specimens on banana mat root systems as Paraputo ensete (Williams & Matile-Ferrero) (Hemiptera: Pseudococcidae) through DNA analysis.

Seasonal modulation of the adrenocortical stress responses in Chilean populations of Zonotrichia capensis - Aaron D. Clark; Elizabeth A. Addis; Rodrigo A. Vásquez; John C. Wingfield (Journal of Ornithology, 2019)

Variation in circulating corticosterone levels is associated with altitudinal range expansion in a passerine bird - Elizabeth A. Addis; Jason E. Davis; Brooks E. Miner; John C. Wingfield (Oecologia, 2011)

Endocrine responsiveness to social challenges in northern and southern hemisphere populations of Zonotrichia - John C. Wingfield; Simone L. Meddle; Ignacio Moore; Shallin Busch; Douglas Wacker; Sharon Lynn; Aaron Clark; Rodrigo A. Vasquez; Elizabeth Addis (Journal of Ornithology, 2007)

Temporal patterns in seedling establishment on pocket gopher disturbances - Tara A. Forbis; Jason Larmore; Elizabeth Addis (Oecologia, 2004)